(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This paper aimed to analyze the value relevance of disclosing research and development (R&D) expenditures in Brazil’s capital market between 2011 and 2015. The study has a documental and quantitative approach and examined a population of 440 public companies listed in B3. Applying Ohlson’s model (1995), data were collected concerning earnings, net revenue, equity, R&D expenditures (2011-2015) and market value (2010-2015), composing a sample of 1,241 observations. These data come from financial statements, explanatory notes and Economatica® database. The analysis used linear regressions with panel data estimation with fixed effects. The hypotheses were rejected because the R&D expenditure disclosure and the investment in R&D expenditures are not value relevant. We concluded that R&D expenditures disclosure and the value applied in R&D activities do not indicate a greater probability to gain competitive advantage in the context of the Brazilian capital market.